1995
DOI: 10.1017/s0950268800052006
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics ofMycobacterium tuberculosiscomplex in Scotland analysed by pulsed-field gel electrophoresis

Abstract: SUMMARYThe results of typing of 121 strains in the Mycobacterium tuberculosis complex by PFGE are presented. Every isolate from patients in Scotland over a 3-month period for M. tuberculosis and for 1 year for M. bovis were included along with several laboratory strains including those of BCG. The PFGE results suggest that the population structure of all the strains in this complex is distinctly simple with limited genetic diversity and also suggest that M. bovis is not a distinct species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…In contrast, Zhang et al [21], using Xbal in PFGE analysis of isolates from the USA, found greater strain diversity. This was interpreted as arising from the more diverse origin of the human population, possibly due to migration, compared to Scotland [22]. In the current study, Xbul was shown to distinguish between unrelated strains cultured from ethnically different populations.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…In contrast, Zhang et al [21], using Xbal in PFGE analysis of isolates from the USA, found greater strain diversity. This was interpreted as arising from the more diverse origin of the human population, possibly due to migration, compared to Scotland [22]. In the current study, Xbul was shown to distinguish between unrelated strains cultured from ethnically different populations.…”
Section: Discussionmentioning
confidence: 48%
“…Some isolates with the same pattern were isolated from patients in different Australian states, but no one strain predominated. Most isolates cultured from patients born in Australia and Northern Europe produced more DNA bands (19)(20)(21)(22) than isolates cultured from patients born in Asian countries such as the . However, a high degree of polymorphism was found amongst isolates of both groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations